Descriptive analysis of municipal policies addressing shade in eight southwest and northeast states in the United States - Buller, David B.; Kinsey, Alishia; Sullivan, Taylor; Gruetter, Phoebe; Morrissey-Basler, Margaret C.; Buller, Ian D.; Heckman, Carolyn J. (Frontiers in Public Health, 2025)
IntroductionShade is an essential environmental feature to prevent heat illnesses and skin cancer. Written policies related to shade were described in municipalities in four southwest and four northeast U.S. states.MethodMunicipal codes, planning documents, and manuals/guidelines from municipalities (N = 48) in eight U.S. states were coded for content related to shade by research assistants. They used a standardized protocol to assign numeric codes to each document to assess type of document, type of shade, location, resource allocation, accountability, and design standards. Results were summarized using descriptive statistics.ResultsThree quarters of municipalities (75.0%) had a policy document that addressed shade, including municipal codes (54.2%), planning documents (29.2%), and manuals/guidelines (12.5%). Protecting from heat (31.3%) was mentioned in policies more than protecting from ultraviolet radiation (8.3%), as was natural shade (56.3%) rather than constructed shade (25.0%). Policies prescribed several design standards, most frequently shade material, proportion of area covered, and attractiveness. Half (50.0%) of municipalities mentioned accountability for shade in the policy, but only a third (35.4%) addressed resource allocation. Regional differences were seen in policy document type, shade type, locations, design standards, and resource allocation.DiscussionMany municipalities had policies that mentioned shade, but only a minority of policies indicated that the purpose of the policy was protection from heat or ultraviolet radiation. In northeast municipalities, which can have local home rule traditions, policies on shade appeared almost entirely in municipal codes. Southwest municipalities often included policies in planning documents that may have less legal force than municipal codes.